Alveolar macrophages and T cells from sarcoid, but not normal lung, are permissive to adenovirus infection and allow analysis of NF-kappa b-dependent signaling pathways. - Conron, M; Bondeson, J; Pantelidis, P; Beynon, H; Feldmann, M; duBois, R; Foxwell, B (2001)
Adenovirus (Adv)-mediated gene transfer requires efficient infection of target cells. The objective of this study was to establish whether alveolar macrophages (AM) and T cells (AT) from sarcoid patients were permissive to infection with Adv vectors and if this property could be used to investigate cytokine gene regulation. Sarcoid and normal bronchoalveolar lavage (BAL) specimens infected with Adv vectors expressing either beta-galactosidase or a green fluorescent protein were analyzed for transgene expression by fluorescence-activated cell sorter (FACS) and direct immunofluorescence, respectively. Expression of surface antigens previously associated with Adv infection, the coxsackie/adenovirus receptor (CAR), alpha v beta 3, and alpha v beta 5 integrins, was also assessed using FACS analysis. Sarcoid AM and AT were found to efficiently express Adv transgenes, unlike AM from normal volunteers, peripheral blood monocytes, and peripheral blood T cells. Cells permissive to Adv infection expressed the CAR and alpha v beta 5 integrin (also alpha v beta 3 integrin for AM). The data indicate that the upregulation of Adv receptors and the ability to infect sarcoid AM and AT are related to the inflammatory environment within the lung. Having demonstrated efficient Adv-mediated transgene delivery to sarcoid AM and AT, a construct encoding porcine I kappa B alpha was then used to investigate the requirement for nuclear factor (NF)-kappa B in the regulation of cytokine gene expression in pulmonary sarcoidosis. Overexpression of I kappa B alpha in sarcoid BAL specimens indicated that tumor necrosis factor-alpha and interleukin (IL)-6 production by AM and interferon (IFN)-gamma production by AT is NF-kappa B dependent, whereas IL-4 production by AT is NF-kappa B independent. This is the first occasion that the requirement for NF-kappa B in IFN-gamma gene expression within primary human T cells has been demonstrated. The results of this study have implications for the future investigation of molecular pathways in inflammatory lung disease.